Enhancement of photoluminescence from iron disilicide on Si(111) substrates with Au layers by controlling microstructures. (9th May 2017) - Akiyama, Kensuke; Matsumoto, Yoshimisa; Funakubo, Hiroshi
Abstract: The photoluminescence (PL) spectrum of iron disilicide (β-FeSi2 ) was enhanced by increasing the density of epitaxial grains grown at 650 °C on Si(111) substrates with a Au layer. The Au–Si liquidus phase obtained from the Au–Si eutectic reaction contributed to the formation of epitaxial β-FeSi2 grains on the Si(111) surface. The density of the epitaxial β-FeSi2 grains on the Si(111) surface decreased with increasing thickness of the Au layer, while the grain size increased from 0.5–2 to 20–50 µm. It is suggested that the excitation volume of the β-FeSi2 is a key point that determines the PL intensity.